Championing The Democratic Intellect - Robinson, Mike (ARCTIC, 1997)
[This brief note discusses the philosophical basis of the Scottish vision of civil society and the Scots championing of Democratic Intellectualism. The Scottish tradition of academic generalism, trust in lay scholars, and the practice of technical and practical competencies is alive at the Arctic Institute and is expressed in the ASTIS database, the journal Arctic, PAR and co-management research. The article notes that intermarriage between Native women and Scotsmen has produced an intermarriage of intellectual traditions, particularly among the Canadian Metis.] . The challenge now before us as citizens is to continue championing the Democratic Intellect, especially in settings such as academia and corporations where the arguments of specialization, hierarchies, and elites still find appeal and adherents. .